حدوثُ العالم وقِدَمُه: دراسۃ مقارنۃ لآراء الکندی والفارابی: Incidence and Antiquity of the World: A Comparative Study of the Views of al-Kindī and al-Fārābī - Muhammad Ishfaq; Dr Raheela Khalid Qureshi; Qammar Aziz (Al-Qamar, 2019)
This paper presents a comparative study of the views of al-Kindī (801-873), a renowned Arab Muslim philosopher hailed as the “father of Arab philosophy” and al-Fārābī (872-950), another distinguished Muslim philosopher called “Second Teacher” following Aristotle known as the “First Teacher, on the incidence and antiquity of the world. It finds that there is much difference between the two philosophers on the referred issue. Al-Kindī believes in the incidence of the cosmos, while al-Fārābī believes in its antiquity. Al-Kindī’s views are thus in line with the traditional religious stance commonly accepted by Christians, Jews, and Muslims on behalf of their religious texts. Al-Fārābī’s denial of the incidence of the world is actually the denial of resurrection, as in his view the world has no end. Islamic religious texts clearly verify the occurrence of the world and reject the notion of its antiquity.